0561 Sleep Disturbance Among COVID-19 Post-hospitalized Patients. (25th May 2022) - Satashia, Parthkumar; Castellanos, Paula; Aleger, Chary; Yin, Mingyuan; Cheung, Joseph
Abstract: Introduction: COVID-19 primarily affects the respiratory system, however, a number of clinical sequela have emerged in patients recovered from COVID-19. Besides the most commonly reported symptoms of fatigue and dyspnea, early studies have found that sleep disturbance is also a common complaint. The aim of this study is to survey for sleep disturbance, degree of fatigue and daytime sleepiness in a group of post-hospitalized COVID-19 patients. Methods: Patients who were discharged from Mayo Clinic hospitals after COVID-19 hospitalization were recruited in this study. Patients who have an existing diagnosis of sleep apnea or other sleep disorders were excluded from this study. Mayo Clinic patients who never had COVID-19 infection, nor a history of sleep disorders or other sleep disorders were also recruited as controls. Patients completed Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), and Fatigue Severity Scale (FSS) questionnaires via REDCap. Wilcoxon rank sum test was used to evaluate the difference between cases and controls in continuous variables and Fisher's exact test was used to compare categorical variables. Multivariable linear regression model was used to evaluate the difference in sleep and fatigue scores between cases and controls with baseline characters adjusted. All tests were two-sided with p value <0.05 considered statistically significant. Results: A total of 62 patients who completed the questionnaires were included in the analysis. Among them, 33 had COVID-19. Cases were significantly older with higher BMI compared to controls. Global PSQI score (median=10 vs 6, p=0.015), ESS total score (median=8 vs 5, p=0.018) and FSS total score (median=30 vs 22, p=0.009) were all significantly higher for cases compared to control patients. After adjusting for age and BMI, the difference stayed statistically significant. The mean difference between cases vs controls was found to be 2.7 (95%CI:0.2-5.2, p=0.038), 2.93 (95% CI: 0.66-5.2, p=0.014), and 12.62 (95% CI:5.22-20.03, p=0.001) for PSQI, ESS, and FSS scores, respectively. Conclusion: Preliminary results showed that sleep disturbance (PSQI) and daytime symptoms (measured by ESS and FSS) are found to be significantly higher among post COVID-19 hospitalized patients compared to controls. Support (If Any): This work is supported by the Mayo Clinic in Florida Department of Medicine Catalyst for Advancing in Academics award and the Mayo Clinic in Florida Research Accelerator for Clinicians Engaged in Research Program.